THE INFLUENCE OF TOTAL THIRD PARTY FUNDS AND INFLATION ON THE ALLOCATION OF FINANCING FOR MICRO, SMALL AND MEDIUM ENTERPRISES AT BANK SUMUT SYARIAH MEDAN KATAMSO BRANCH - ., Lisnawati; Indah Lestari, Annio; Syarvina, Wahyu (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
This study aims to determine the effect of the amount of third-party funds and inflation on the allocation of financing for micro, small and medium enterprises at the Sharia Bank of North Sumatra, Medan Katamso branch. This study uses a quantitative method and uses secondary data on the monthly financial reports of Bank Sumut Syariah which were published for 2018-2022, and BPS data for 2018-2022. Data is processed through the SPSS 25 program with multiple linear regression methods, with consideration of R2, T-test, F-test, and classical assumption tests. The results of this study indicate that Third Party Funds (DPK) have a positive effect on the allocation of MSME financing at PT Bank SUMUT Syariah Medan Katamso of (0.872) with a very large value in the 2018-2022 period. Inflation has a positive and small effect on the allocation of MSME financing for PT Bank SUMUT Syariah Medan Katamso during the 2018-2022 period, amounting to (0.083). Simultaneously DPK (Third Party Funds), Inflation has a significant effect on the MSME financing allocation of PT Bank SUMUT Syariah Medan Katamso during the 2018-2022 period